Development of a bioorthogonal fluorescence-based assay for assessing drug uptake and delivery in bacteria. Issue 25 (23rd May 2022) - Ooi, Jocelyn M. F.; Fairhall, Jessica M.; Spangler, Benjamin; Chong, Daniel J. W.; Feng, Brian Y.; Gamble, Allan B.; Hook, Sarah
Abstract : Bioorthogonal alkyne–azide and alkyne–tetrazine chemistries were used to assess drug uptake in bacteria. Azido-drug reacts with streptavidin bound alkyne-biotin within bacteria, the remaining unreacted alkyne is then quantified with a tetrazine-dye. Abstract : Bioorthogonal chemistry can facilitate the development of fluorescent probes that can be used to sensitively and specifically detect the presence of biological targets. In this study, such an assay was developed to evaluate the uptake and delivery of antimicrobials into Escherichia coli, building on and extending previous work which utilised more resource intensive LCMS detection. The bacteria were genetically engineered to express streptavidin in the periplasmic or cytoplasmic compartments, which was used to localise a bioorthogonal probe (BCN-biotin). Azido-compounds which are delivered to these compartments react with the localised BCN-biotin–streptavidin in a concentration-dependent manner via a strain-promoted alkyne–azide cycloaddition. The amount of azido-compound taken up by bacteria was determined by quantifying unreacted BCN-biotin–streptavidin via an inverse electron demand Diels–Alder reaction between remaining BCN-biotin and a tetrazine-containing fluorescent dye. Following optimisation and validation, the assay was used to assess uptake of liposome-formulated azide-functionalised luciferin and cefoxitin. The results demonstrated that formulation into cationic liposomes improved the uptake of azide-functionalised compounds into the periplasm of E. coli, providing insight on the uptake mechanism of liposomes in the bacteria. This newly developed bioorthogonal fluorescence plate-reader based assay provides a bioactivity-independent, medium-to-high throughput tool for screening compound uptake/delivery.